INDONESIAN RELIGIOUS EVOLUTION: Applying Bellah’s Theory in Indonesian Context - Murtafi Haris, Achmad (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2013)
Religious adherents usually pay no attention to the evolution of religions. They believe in religion as a matter of taken for granted without considering the historical aspect which in the end becomes his believed religion. Robert Bellah has clarified the historicity of religion and found the evolutional process of religions which are similar to the evolution of human civilization. His research finally ends with the conclusion that religions evolve and develop from the simple entity to the complex one. Bellah has classified religious evolution into five periods. Firstly is the period of Primitive Religion which is then followed by Archaic Religion, Historical religion, Early Modern Religion and comes in the end the period of Modern Religion. Each period has distinct characteristic which is coincident with the phase of human civilization of the time. Having paid attention to Bella’s insight upon religious evolution this paper tries to implement the theory in the context of Indonesia. Some of paper’s invention discloses the different way of religious participation among modern Indonesian Muslims who are no longer dependent on religious institutional interpretation. Key Word: religions, evolution, civilization, Indonesia.